2011
DOI: 10.1902/jop.2011.100768
|View full text |Cite
|
Sign up to set email alerts
|

iNOS‐Derived Nitric Oxide Stimulates Osteoclast Activity and Alveolar Bone Loss in Ligature‐Induced Periodontitis in Rats

Abstract: Background Inflammatory stimuli activate inducible nitric oxide synthase (iNOS) in a variety of cell types, including osteoclasts (OC) and osteoblasts, resulting in sustained NO production. In this study, we evaluate the alveolar bone loss in rats with periodontitis under long-term iNOS inhibition, and the differentiation and activity of OC from iNOS-knockout (KO) mice in vitro. Methods Oral aminoguanidine (an iNOS inhibitor) or water treatment was started 2 weeks before induction of periodontitis. Rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 52 publications
(68 reference statements)
5
49
0
2
Order By: Relevance
“…Indeed, the expression levels of IL-6, IL-12, IFN-c, and iNOS were upregulated in mouse BMMs by R848 treatment, while the expression of IFN-b mRNA was not upregulated, but consistently expressed in the BMMs. Among these genes, IL-6 has been shown to promote osteoclast differentiation (Herrera et al 2011;Lee et al 2004;O'Brien et al 2005;Udagawa et al 1995), while iNOS, IL-12, IFN-b, and IFN-c inhibit it (Zheng et al 2006, Horwood et al 2001Takayanagi et al 2002;Takayanagi et al 2000). Therefore, we added neutralizing antibodies against these molecules and found that neutralization of IFN-b by the antibody partially recovered osteoclast differentiation inhibited by R848.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the expression levels of IL-6, IL-12, IFN-c, and iNOS were upregulated in mouse BMMs by R848 treatment, while the expression of IFN-b mRNA was not upregulated, but consistently expressed in the BMMs. Among these genes, IL-6 has been shown to promote osteoclast differentiation (Herrera et al 2011;Lee et al 2004;O'Brien et al 2005;Udagawa et al 1995), while iNOS, IL-12, IFN-b, and IFN-c inhibit it (Zheng et al 2006, Horwood et al 2001Takayanagi et al 2002;Takayanagi et al 2000). Therefore, we added neutralizing antibodies against these molecules and found that neutralization of IFN-b by the antibody partially recovered osteoclast differentiation inhibited by R848.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is known to induce osteoclast differentiation of macrophages (32, 33). In the present study, very high levels of NO were observed as macrophages differentiated into osteoclasts (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Inducible nitric oxide synthase (iNOS) is well known for the contribution to osteoclast activity and alveolar bone loss. Nitric oxide (NO) mediates adaptive bone formation, protects osteocytes against apoptosis and mediates osteoclastic activity (49)(50)(51). GO results enlightened the role of miRNA in regulating nitrogen compound related genes and furthermore, in regulating bone destruction and remolding.…”
Section: Discussionmentioning
confidence: 99%